2006
DOI: 10.1016/j.epsl.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Chains, clumps, and strings: Magnetofossil taphonomy with ferromagnetic resonance spectroscopy

Abstract: Magnetotactic bacteria produce intracellular crystals of magnetite or greigite, the properties of which have been shaped by evolution to maximize the magnetic moment per atom of iron. Intracellular bacterial magnetite therefore possesses traits amenable to detection by physical techniques: typically, narrow size and shape distributions, single-domain size and arrangement in linear chains, and often crystal elongation. Past strategies for searching for bacterial magnetofossils using physical techniques have foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
189
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(214 citation statements)
references
References 45 publications
21
189
4
Order By: Relevance
“…Magnetosome chains have remarkable magnetic properties (5,6,9), which have been used to identify bacterial magnetofossils in sediments. Although previous studies demonstrated that observations by electron microscopy and/or magnetic measurements could detect bacterial magnetofossils in natural samples (9)(10)(11)(12)(13), the chain structure is generally lost during sediment aging owing to degradation of organic matter assembling magnetosomes (9,14). This strongly complicates the identification of the bacterial magnetofossils.…”
mentioning
confidence: 83%
“…Magnetosome chains have remarkable magnetic properties (5,6,9), which have been used to identify bacterial magnetofossils in sediments. Although previous studies demonstrated that observations by electron microscopy and/or magnetic measurements could detect bacterial magnetofossils in natural samples (9)(10)(11)(12)(13), the chain structure is generally lost during sediment aging owing to degradation of organic matter assembling magnetosomes (9,14). This strongly complicates the identification of the bacterial magnetofossils.…”
mentioning
confidence: 83%
“…We reanalyzed sediments from one of their drill cores, from Ancora, New Jersey, using ferromagnetic resonance (FMR) spectroscopy, a technique recently adapted for the identification of fossil magnetotactic bacteria [Kopp et al, 2006]. The results, confirmed by electron microscopy, indicate that the magnetic properties of the clay are produced by magnetofossils, not the impact fallout condensate proposed by Kent et al This finding is the first identification of magnetofossils in ancient sediments by FMR and validates the use of the technique for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…[17] FMR spectroscopy is an electron spin resonance technique capable of assessing the magnetic anisotropy, magnetic interactions, and morphological heterogeneity of magnetic particles in bulk samples [Kopp et al, 2006]. It is thus ideally suited for distinguishing among (1) detrital magnetite, (2) isolated particles of equidimensional magnetite, and (3) magnetofossils, which are frequently elongate and often preserved in chains.…”
Section: Characterization Of Magnetic Particlesmentioning
confidence: 99%
See 2 more Smart Citations